PELAKSANAAN MANAJEMEN WAKIL KEPALA SEKOLAH BIDANG KESISWAAN DALAM PENINGKATAN PROSES PEMBELAJARAN (STUDI KASUS DI SMP NEGRI 34 OKU) - Fathur Rahman (UNISAN JURNAL, 2023)
The management of the Vice Principal for Student Affairs is very important in improving the quality of the learning process in schools. Good planning, organizing, implementing and supervising will ensure that all activities are well coordinated and run according to predetermined standards. This will help in improving the quality of service learning processes in schools and have a positive impact on students. Therefore, the Vice Principal for Student Affairs must have good management skills in order to provide the best service for students in the learning process at school. The success of an organization including school education institutions in a competitive environment is certainly inseparable from how the school's ability to find out and meet needs and provide good service, especially in the learning process effectively. Efforts to serve education users (students) are an important strategy for institutions to achieve quality and quality education because service to students will provide an assessment response to educational institutions. And with the fulfillment of students' needs through good service they will feel satisfaction. Therefore, it is deemed necessary to conduct research regarding the service of the learning process at SMP Negeri 34 OKU and the efforts in it. The formulation of the research problem in general is: how to plan, organize, implement, and supervise the management of the vice principal of student affairs in improving the service of the learning process at SMP Negeri 34 OKU The method used in this research is descriptive qualitative research method. Where trying to reveal the reality or truth behind the symptoms recorded sensory in the interpretive paradigm. In this study, the researcher acted as a key instrument in addition to other supporting instruments such as interview guides, observation guides and audio and video recording tools. Researchers conducted research at SMP Negeri 34 OKU, where the subjects or data sources in this study were field teachers, deputy student affairs and school principals. Data collection techniques in this study were interviews and documentation techniques. The data analysis technique has four stages, namely data collection, data reduction, data presentation and the last is drawing conclusions. The results of the study show that planning regarding student management is prepared on the basis of school capabilities and meets the needs of students and the demands of the times. The organizing process is carried out by providing coaching, guidance and special services as well as responsibility towards students themselves, by monitoring and training activities on empowerment and the potentials of students so that students' goals are achieved and they love their school environment. The implementation process is carried out by carrying out special coaching for students who have special interests and talents. Evaluation and supervision are carried out directly by the Principal and Deputy Principal for Student Affairs and assisted by other staff teachers, with the aim of ensuring the implementation of the student planning program that has been carried out, and monitoring deviations that occur.